Diffusion imaging of the brain: technical considerations and practical applications - Norris, David G. (Diffusion Fundamentals, 2005)
This chapter presents a brief introduction to the application of diffusion-weighted magnetic resonance imaging (MRI) to in vivo studies. Diffusion-weighted MRI has found application both in the clinic, and in basic neuroscience. In the former situation it is primarily used for the detection of brain lesions, in particular infarcted regions. The ability to follow fibre tracts in white matter via diffusion tensor imaging has also made this methodology of interest to the neurosurgeon wishing to avoid severance of essential fibre tracts, but also of interest to the cognitive neuroscientist exploring anatomical connectivity in the brain. The chapter starts with a brief recap of the theory of diffusionweighted MRI and moves on to examine the two major experimental confounds, eddy currents and bulk motion. Current correction schemes for these problems are touched upon. Diffusion anisotropy is introduced as a potential source of artefacts for lesion detection in white matter, and the diffusion tensor model presented. The chapter concludes with a short introduction to fibre tracking.